Belajar Pencerminan dengan Menggunakan Permainan Bom-Boman di Kelas VII - Sri Hartati; Zulkardi Zulkardi; Yusuf Hartono (JRPM (Jurnal Review Pembelajaran Matematika), 2018)
This study produces a learning trajectory in transformation geometry, specifically on reflection using a game called “bom-boman”. This study using PMRI, the Indonesian version of realistic mathematics education. Subjects of this study are 36 seventh grade students of SMP Negeri 24 Palembang. This study using a design research approach with conducted in three stages: preliminary design, the design experiment (pilot experiment & teaching experiment), and retrospective analysis. Data were collected by observations, interviewing the student, collecting student worksheet, and documentation of classroom event and group works. Hypothetical Learning Trajectory (HLT) has been designed then compared to Actual Learning Trajectory (ALT) during the learning process. Retrospective analysis shows that student’s learning trajectories using the game help students to understand transformation geometry in reflection.